Information seeking and communication during forced migration: An empirical analysis of refugees' digital media use and its effects on their perceptions of Germany as their target country. (August 2020) - Emmer, Martin; Kunst, Marlene; Richter, Carola
There is a common perception that 'every refugee carries a smartphone', but research on this phenomenon is limited. We conducted a representative survey of 400 refugees to Germany which provides insight into their use of digital media in preparation for and during forced migration. We also asked whether digital media shaped images of and expectations about the refugees' target country Germany. The data show that refugees are not a homogeneous group and that usage patterns depend on regional origins. Internet use also contributed to a positively biased perception of Germany, but the effect of traditional media use was stronger.